Twenty-Five Years of Innovation and Knowledge Sharing: The Legacy and Future of the International Review of Research in Open and Distributed Learning - Anderson, Terry; Cookson, Peter S.; Henderson, Serena; McGreal, Rory (International Review of Research in Open and Distributed Learning, 2025)
Since its founding in 2000 by Athabasca University, the International Review of Research in Open and Distributed Learning (IRRODL) has emerged as a leading platform for the dissemination of scholarly work in open and distributed learning. This article revisits IRRODL’s foundational goals, the institutional support that facilitated its creation, and its evolution over 25 years. Through this retrospective, we celebrate the journal’s achievements and examine its future as a freely accessible repository of information and knowledge for practitioners and researchers in open and distributed learning.